Action and perception in social contexts: intentional binding for social action effects - Pfister, Roland; Obhi, Sukhvinder S.; Rieger, Martina; Wenke, Dorit (Frontiers in Human Neuroscience, 2014)
The subjective experience of controlling events in the environment alters the perception of these events. For instance, the interval between one’s own actions and their consequences is subjectively compressed – a phenomenon known as intentional binding. In two experiments, we studied intentional binding in a social setting in which actions of one agent prompted a second agent to perform another action. Participants worked in pairs and were assigned to a “leader” and a “follower” role, respectively. The leader’s key presses triggered (after a variable interval) a tone effect and this tone served as go signal for the follower to perform a keypress as well. Leaders and followers estimated the interval between the leader’s keypress and the following tone, or the interval between the tone and the follower’s keypress. The leader showed reliable intentional binding for both intervals relative to the follower’s estimates. These results indicate that human agents experience a pre-reflective sense of agency for genuinely social consequences of their actions.